The relationship between corporate independence and firm performance: the case of public listed firms in Malaysia. - Wagner, Karl; Fard, Pooyan Yousefi (2009)

(untitled)
This paper examines the relationship between board independence and firm performance in Malaysia. The Malaysian Code of Corporate Governance states that at least one third of board members must be independent. Hence, this evolves the question of whether increased board independence can contribute to better performance. This study proves that those corporations which have more independent board members(more than one third of board members which is obligatory)have better firm performance. We included randomly selected 120 public listed companies in Malaysia’ Stock Exchange Board (KLSE), where the performance is measured for the financial year 2006. While this work has been successfully established this positive relationship, it acknowledges the fact, that there are shortcomings. They include only three independent variables, such as independent board members, board size and firm size. Furthermore, the study is only done for one year, and it only involves 120 companies. Although the number of companies is enough to represent corporate Malaysia, a larger sample size will provide better justification for the empirical findings. Considered all these facts, we can provide strong evidence and conclude that a higher number of independent board members may significantly lead to higher business performance.